Answers

The Brainliest Answer!
2015-07-14T07:22:45+05:30
IF IT IS AC^2 THEN THE ANSWER IS

FROM TRIANGLE ABC
              BC = 2BM

FROM TRIANGLE ABC

BY PYTHAGORAS THEOREM 

AC^2 = AB^2+BC^2
I.E AB^2 = BC^2-AC^2     ----(1)

FROM TRIANGLE ABM

AM^2 = AB^2+BM^2       (BY PYTHAGORAS THEOREM)
I.E AB^2 = BM^2-AM^2    ------(2)

FROM (1) & (2)

BC^2-AC^2 = BM^2-AM^2
BC^2-BM^2+AM^2 = AC^2
(2BM)^2-BM^2+AM^2 = AC^2        [BC = 2BM]
4BM^2-BM^2+AM^2 = AC^2
3BM^2+AM^2 = AC^2

AC^2 = AM^2+3BM^2

HENCE PROVED
2 5 2